2016
DOI: 10.1007/s00442-016-3700-8
|View full text |Cite
|
Sign up to set email alerts
|

Using a model based fourth-corner analysis to explain vegetation change following an extraordinary fire disturbance

Abstract: In ecosystems where large-scale disturbances are infrequent, the mode of succession may be difficult to discern and floristic surveys alone cannot be used determine the underlying processes causing vegetation change. To determine the causes of vegetation change in response to a large-scale fire event, we combined traditional floristic survey data, plant functional traits and environmental variables in a model-based solution to the fourth-corner problem. This approach allowed us to describe the trait-environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
1
2
0
1
Order By: Relevance
“…However, extreme events, such as fires, can have very important effects on the structure and composition of grasslands (Venn et al 2016). In the study area, a collapse of the vegetation cover just after the event was observed, followed by a recovery that favored the abundance of graminoids species with a large seed bank, as reported by Buma (2012).…”
Section: Discussionsupporting
confidence: 59%
“…However, extreme events, such as fires, can have very important effects on the structure and composition of grasslands (Venn et al 2016). In the study area, a collapse of the vegetation cover just after the event was observed, followed by a recovery that favored the abundance of graminoids species with a large seed bank, as reported by Buma (2012).…”
Section: Discussionsupporting
confidence: 59%
“…Of particular issue for Australian alpine regions, is increasing fire severity and frequency with climate change (Hennessy et al 2005;Zylstra 2018), as these regions have historically experienced few fires (Dodson et al 1994;Kirkpatrick and Bridle 2013;Williams et al 2008). While some alpine vegetation communities have recovered from fire in the past, specialist communities and cryophilic species had limited capacity to recover post fire (Kirkpatrick et al 2010;Venn et al 2016). In the past decades, fires in the Australian Alps are becoming hotter, more frequent and covering larger areas with fires burning into alpine areas previously thought to have low flammability.…”
Section: Influence Of Climatic Drivers and Regional Implicationsmentioning
confidence: 99%
“…Tuttavia eventi straordinari come l'incendio oggetto di studio, possono avere degli effetti molto importanti sulla struttura e la composizione specifica delle praterie. Alcuni studi hanno dimostrato un crollo della copertura della vegetazione appena dopo l'evento, seguito da un recupero che ha favorito l'abbondanza di graminacee (Venn et al 2016).…”
Section: Discussioneunclassified